2011
DOI: 10.1002/mnfr.201000572
|View full text |Cite
|
Sign up to set email alerts
|

Release of lipophilic molecules during in vitro digestion of soy protein‐stabilized emulsions

Abstract: Bioactive molecular structure and co-administration influenced the transfer behaviour, with implications for foods designed to optimize health benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 43 publications
2
25
1
Order By: Relevance
“…29 Also, BC and other highly lipophilic molecules studied were observed to concentrate in emulsion droplets during digestion, leading to relatively less BC transfer compared to the extent of lipid hydrolyzed. 30 The same concentration effect was observed for the COE samples in the present study. In contrast, for the SLN, the percentage of BC transfer was similar to the percentage of lipid hydrolysis within each system (Fig.…”
Section: Fig 5 Andsupporting
confidence: 89%
See 1 more Smart Citation
“…29 Also, BC and other highly lipophilic molecules studied were observed to concentrate in emulsion droplets during digestion, leading to relatively less BC transfer compared to the extent of lipid hydrolyzed. 30 The same concentration effect was observed for the COE samples in the present study. In contrast, for the SLN, the percentage of BC transfer was similar to the percentage of lipid hydrolysis within each system (Fig.…”
Section: Fig 5 Andsupporting
confidence: 89%
“…29 Also, we recently showed that the physical properties and molecular structure of oil-soluble bioactives played a crucial role in their transfer from an oil-in-water emulsion to the aqueous phase during simulated digestion. 30 The most highly lipophilic molecules studied (bcarotene and coenzyme Q 10 ) tended to remain in the oil droplet, in contrast to vitamin D 3 and phytosterols, which solubilized more readily into the aqueous phase. However, a better understanding of the transfer processes involved during lipolysis and aqueous phase solubilization is required.…”
Section: Introductionmentioning
confidence: 97%
“…Lipid-based matrices are known to improve the bioavailability of hydrophobic bioactives, which make these matrices especially interesting as encapsulation systems. Recent advances have shown that one of the approaches to improve the solubility and bioavailability of poorly soluble substances, such as carotenes and tocopherols, is to incorporate these compounds in lipid-based encapsulation systems (Helgason et al 2008, Helgason et al 2009Nik et al 2011;Shukat and Relkin 2011;Wang et al 2012). Several structured lipid-based delivery systems are available to encapsulate, protect and deliver the hydrophobic bioactive compounds in the form of lipid droplets (emulsions, microemulsions, nanoemulsions, multiple emulsions), liposomes, coated particles (multilayer emulsions, colloidosomes) and solid lipid particles (McClements 2010;McClements and Li 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the surfactant type pronouncedly affected the stability of lipid particles during in vitro digestion. Whey protein stabilized interfacial layers exerted the lowest stability (droplet size increased from 0.6 to 18 μm) in the gastric phase, probably due to their susceptibility to pepsin, disintegrating the interfacial layers, promoting droplet flocculation Nik et al, 2011). Emulsion exposure to duodenal and intestinal fluids remarkably reduced particle size, with the WPI-and SSPSstabilized ones showing the strongest response.…”
Section: Llcs Encapsulated Carotenoidsmentioning
confidence: 98%